TORSADE DE POINTES - Latulola, Shinta M; Lefrandt, Reginald L (UNIVERSITAS SAM RATULANGI, 2012)
Abstract: Torsade de pointes (TdP) is a disturbance of heart rhythme, a ventricular tachycardia polymorphic type, with irregular ventricle contractions more than 200-250 per minute, and the QRS axis shows a twisting of points.We reported a 63-year-old female with torsade de pointes and a long QT syndrome. The causes of this TdP were multifactorial, such as electrolyte imbalance (hypokalemia and hypomagnesemia), medicine (amiodarone and digoxin), and chronic heart diseases. The management of this patient was defibrillation, magnesium supply, cease of amiodarone and digoxin therapy, correction of electrolyte imbalance, supression of EADs, and heart failure treatment.Key words: torsade de pointes, arrythmia, multifactorialAbstrak: Torsade de pointes (TdP) adalah gangguan irama jantung berupa takikardi ventrikuler tipe polimorfik, dimana ventrikel berkontraksi lebih dari 200 sampai 250 kali per menit secara tidak beraturan dengan sumbu axis QRS yang bervariasi, membentuk gambaran seperti kumparan (twisting of points). Kami melaporkan kasus seorang perempuan dengan torsade de pointes dan long QT syndrome yang didapat. Faktor penyebab multifaktorial berupa gangguan elektrolit (hipokalemia dan hipomagnesemia), obat-obatan (amiodaron dan digoksin), serta adanya penyakit jantung kronik. Penanganan pada kasus ini terdiri dari defibrilasi, pemberian magnesium, penghentian pemberian amiodaron dan digoksin, koreksi ketidakseimbangan elektrolit, supresi EADs, serta penanganan gagal jantung.Kata kunci: torsade de pointes, aritmia, multifaktorial